Handbook of research on crisis leadership in organizations (Northampton Edward Elgar, 2013)
With contributions from many of the leading researchers in the field, the Handbook of Research on Crisis Leadership in Organizations summarizes much of the theory, research, and opinion about various facets of crisis leadership in order to advance this emerging field. It recognizes that crises have become an almost inevitable part of organizational life, and describes how leaders can facilitate people getting through the crisis.
Includes index
Keywords: Crisis Leadership